2019
DOI: 10.1002/humu.23820
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of massively parallel reporter assays enables prediction of regulatory function across cell types

Abstract: Deciphering the potential of noncoding loci to influence gene regulation has been the subject of intense research, with important implications in understanding genetic underpinnings of human diseases. Massively parallel reporter assays (MPRAs) can measure regulatory activity of thousands of DNA sequences and their variants in a single experiment. With increasing number of publically available MPRA data sets, one can now develop data‐driven models which, given a DNA sequence, predict its regulatory activity. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…The selected oligonucleotides were generated and cloned upstream of a minimal promoter (mP) and EGFP reporter gene into a lentivirus-based enhancer assay vector (Figure 2B) as previously described (Inoue et al, 2017). Although the sequences are assayed in the context of enhancer activity in this assay, previous work has shown that it also provides a good indication for promoter activity (Kreimer et al, 2017(Kreimer et al, , 2019Melnikov et al,2014). Each individual CRS was designed to be associated with 90 different 15-bp barcodes, thus allowing robust evaluation of the pertaining expression output and to correct for site of integration biases (Ashuach et al, 2019;Inoue et al, 2017).…”
Section: Lentimpra Identifies Regulatory Regions That Are Active During Neural Inductionmentioning
confidence: 99%
“…The selected oligonucleotides were generated and cloned upstream of a minimal promoter (mP) and EGFP reporter gene into a lentivirus-based enhancer assay vector (Figure 2B) as previously described (Inoue et al, 2017). Although the sequences are assayed in the context of enhancer activity in this assay, previous work has shown that it also provides a good indication for promoter activity (Kreimer et al, 2017(Kreimer et al, , 2019Melnikov et al,2014). Each individual CRS was designed to be associated with 90 different 15-bp barcodes, thus allowing robust evaluation of the pertaining expression output and to correct for site of integration biases (Ashuach et al, 2019;Inoue et al, 2017).…”
Section: Lentimpra Identifies Regulatory Regions That Are Active During Neural Inductionmentioning
confidence: 99%
“…There had also been only one previous expression regulatory variant challenge, in CAGI4 (Kreimer et al, ). CAGI5 has a new expression regulatory challenge (Shigaki et al, ), and there are also two participant papers (Dong & Boyle, ; Kreimer, Yan, Ahituv, & Yosef, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although H3K27ac has been the most widely used chromatin mark to identify enhancers, this feature was outperformed by fifteen different experimental and sequence features included in the meta-analysis. Nevertheless, overlap with H3K27ac signal demonstrated greater predictive value for enhancer activity than all other histone modification profiles tested, with the exception of H3K4me2 and pan-histone H2 acetylation (Kreimer et al 2019).…”
Section: Massively Parallel Reporter Assaysmentioning
confidence: 81%
“…MPRA data can also be used to determine the sequence or chromatin features that best identify active enhancers. A recent meta-analysis combined the quantitative transcript data from five different MPRAs that each tested ~2000 putative enhancer sequences in a total of 6 different cell types (Kreimer et al 2019). This analysis compared 56 different chromatin features in overall predictive capacity and found DNase I signal and the number of different TFs bound by ChIP-seq within the sequence most accurately predicts enhancer activity (Kreimer et al 2019).…”
Section: Massively Parallel Reporter Assaysmentioning
confidence: 99%
See 1 more Smart Citation